Good Governance and Neo-Liberal Public Policy Formation - Jefri Leo Chandra; Adriana Grahani Firdausy (MultiTech Publisher, 2023)
Since the last few years, good governance discourse has colonized public discourse on reform and democratization in Indonesia. This article aims to deconstruct the good governance discourse itself, what is actually wrong or perhaps even what is often said about good governance. This article attempts to show the inclusion of neo-liberal ideas in the imagination of political, economic and social changes that took place in the final years of Suharto's leadership in the early 1990s. As will be shown in this article, this movement labeled governance is actually increasingly moving away from the true spirit of governance. In short, the good governance movement in Indonesia actually deviated from the spirit of governance which prioritizes accommodation, cooperation and synergy in equality between actors. This brings about a process of marginalizatio of economic, social, cultural and political policies that are in line with neo-liberal values.